Handling the Inflation by Syrian Daily Press Content Analysis Study - Hme, Marwan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to monitor and analyze press coverage of the issue of price inflation in the economic pages in the Syrian daily newspapers (Al-thawra, Al-Baath, Al-watan), and evaluate the reality of their performance and their impact on the citizen through the editorial arts used in addressing the phenomenon of inflation, which counts large numbers of citizens. In order to achieve these goals, the researcher used the descriptive approach and style of content analysis. Research revealed that the Syrian daily press to address the problem of rising prices is dominated by news of handling which is based on reports and stories of news type. The research also revealed that the headlines topped ranked first among the means of highlighting used in addressing the phenomenon of inflation, and all the pictures published were free of comments and annotations and descent to the source. Research has shown, too, that the sources of published material about inflation are primarily delegates and reporters, officials actually about interpretation and opinion articles in newspapers studied, then the ministries and official departments. Also, it indicated that the geographical scope to address the newspapers to inflation was limited to the city of Damascus and its suburbs to other cities and the countryside of the Syrian account.